Role of neurokinin-1 expressing neurons in the locus coeruleus on ventilatory and cardiovascular responses to hypercapnia - de Carvalho, Debora [UNESP]; Bicego, Kenia C. [UNESP]; de Castro, Olagide W.; da Silva, Glauber S. F.; Garcia-Cairasco, Norberto; Gargaglioni, Luciane Helena [UNESP] (Elsevier B.V., 2010)
We assessed the role of NK-1 receptors (NK1R) expressing neurons in the locus coeruleus (LC) on cardiorespiratory responses to hypercapnia. To this end, we injected substance P-saporin conjugate (SP-SAP) to kill NK-1 immunoreactive (NK1R-ir) neurons or SAP alone as a control. Immunohistochemistry for NK1R, tyrosine hydroxylase (TH-ir) and Glutamic Acid Decarboxylase (GAD-ir) were performed to verify if NK1R-expressing neurons, catecholaminergic and/or GABAergic neurons were eliminated. A reduced NK1R-ir in the LC (72%) showed the effectiveness of the lesion. SP-SAP lesion also caused a reduction of TH-ir (66%) and GABAergic neurons (70%). LC SP-SAP lesion decreased by 30% the ventilatory response to 7% CO(2) and increased the heart rate (fH) during hypercapnia but did not affect MAP. The present data suggest that different populations of neurons (noradrenergic, GABAergic, and possibly others) in the LC express NK1R modulating differentially the hypercapnic ventilatory response, since catecholaminergic neurons are excitatory and GABAergic ones are inhibitory. Additionally, NK1R-ir neurons in the LC, probably GABAergic ones, seem to modulate fH during CO(2) exposure, once our previous data demonstrated that catecholaminergic lesion does not affect this variable. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: A6; SP-SAP; CO(2); Chemosensitivity; Breathing; GABA; Noradrenaline